Tackling coloniality in EdTech: Making your offering inclusive and socially just - Adam, Taskeen; Moustafa, Nariman; Sarwar, MoizzaBinat (EdTech Hub, 2022)
On 29 June 2022, Bertha Centre, EdTech Hub, Open Development & Education and the Overseas Development Institute (ODI) presented a workshop on Tackling Coloniality in EdTech. The workshop was hosted by Ntombini Marrengane (Bertha Institute). This slide deck shares the resources and activities used at the workshop, in the hope that it inspires others to host similar workshops that critically reflect on how coloniality can be embedded in EdTech designs, projects, programmes, processes, structures, values, knowledge systems, and philosophies.
ZenodoArchiveID: 7612943 ZenodoArchiveConcept: 7612942 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7612943 10.53832/edtechhub.0147 10.53832/edtechhub.0150 2405685:3QV8PAED
Keywords: _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found